Mechanization, automation and robotics for the food crop production - Wan Ishak Wan Ismail (Malaysian Society of Plant Physiology, 2014)
Lower agricultural productions are attributed by lack of commercialization, low technology efficiency, productivity and coupled with transfers of resources such as manpower, land and capital out of the agricultural sector into manufacturing sector. It is envisaged that the effect of labour shortage in the agricultural sector can be reduced by increasing productivity of existing labour through mechanization. Mechanization of agricultural activities will increase the productivity per farm worker and will change the character of farm work, making it less ardous and more attractive. Engineering input into agro-based industries are needed at all phases of production. By introducing the robotic technology coupled with computer control to automate the robot arm more manpower can be reduced. With the introduction of information technology, the farmers will become more knowledgeable about farming. With the advent of satellites, the Geographical Information System, (GIS) can served as an important database tool for improved farming. The Global Positioning System, (GPS) find its importance with precision agriculture or precision farming. Agriculture will go into a new era of intelligent farming from farm mechanization with the birth of the precision agriculture.